Genetic Diversity Assessment of Brinjal Germplasm for Varietal Improvement (Journal of Science and Technology Research, 2024)
Forty-one (41) brinjal (Solanum melongena L.)  germplasm of were evaluated at the field of Plant Genetic Resources Centre, BARI, Gazipur to identify the salient features and to assess genetic divergence of germplasm in the time of rabi season 2021-22. Distinct variation was observed in qualitative characters among the germplasm except two characters i.e. fruit cross section and fruit position. For the characters length breath ratio and calyx prickles of fruit, the topmost variation was found. In case of quantitative characters, variation was noticed maximum in the length of fruit (CV-43.79%), afterwards individual weight of fruit (CV-32.91%) and yield plant-1 (CV-30.12%). The highest number of germplasm was dispersed into cluster I. Among the clusters, cluster II and cluster III were occupied by ten germplasm, respectively. Cluster mean value was noted maximum in cluster II for the characters days required for 50% flowering (67.90%), plant height (97.97 cm), individual fruit weight (107.35 g), and yield plant-1 (2.51%). Among the principal components, 27.28% of the total variation interpreted by the first PC and the second PC clarified 22.36% of the variation. In the biplot, germplasm NF-15, NF-20, NF-13, NF-7, NF-4, NF-25, NF-16, and NF-2 etc. were independently far away from the studied germplasm by keeping a distance from the centroid. These results displayed distinctiveness and divergence of germplasm as regards of the studied traits. Populations with high values for the first eigen vectors are individual fruit weight (0.642), yield plant-1 (0.564), and width of fruit (0.313), these characters were the utmost significant contributors towards the diversity of  germplasm in PC1. The germplasm NF-4 (3.45 kg), NF-30 (3.38 kg), and NF-25 (3.08 kg) were higher yielders among the tested germplasm and may be used for future varietal improvement of brinjal.J. of Sci. and Tech. Res. 5(1): 21-29, 2023